Clinical effect of Xuebijing combined with thymosinα1 on patients with severe pneumonia complicated with sepsis and its effect on serum inflammatory factors - Chen, Yan; Zhou, Lijuan; Wang, Jing; Gu, Tianhao; Li, Shuqing (Cellular and Molecular Biology, 2022)
This study aimed to research the clinical effect of Xuebijing combined with thymosin α1 on patients with severe pneumonia complicated with sepsis, and its effect on serum inflammatory factors. For this purpose, 81 cases of severe pneumonia complicated with sepsis were collected. All patients were given early treatments. 41 cases who received Xuebijing injection by intravenous drip were selected as the control group. 40 cases who were treated through subcutaneous injection of thymosin α1 based on Xuebijing injection by intravenous drip were selected as the study group. The body temperature, respiration, heart rate, leukocytes, other general conditions, blood gas indexes, serum IL-6, TNF-α and CRP levels, bacterial clearance rate and therapy effect were recorded and compared before and after treatment. Results showed that after treatment, the body temperature, respiration, heart rate, leukocytes and other general conditions of the study group were lower than those in the control group (all p<0.05). The blood gas indexes pH and PaCO2 levels of the study group were lower than those of the control group. The levels of serum interleukin-6 (IL-6), serum tumor necrosis factor α (TNF-α) and C-reactive protein (CRP) in the study group were lower than those in the control group (all p<0.05). The bacterial clearance rate of the study group was lower than that of the control group (all p<0.05). The total effective rate of treatment of patients in the study group was higher than that of patients in the control group (all p<0.05). In general, Thymosin α1 and Xuebijing injection can improve the therapy effect of severe pneumonia complicated with sepsis, improve the hemorheology condition of patients, effectively remove bacteria and reduce the expression level of serum CRP, TNF-α, IL-6, IL-8 and other inflammatory factors in patients, which is worthy of clinical promotion.